2021
DOI: 10.1007/s10834-021-09796-y
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Adverse Childhood Experiences and Financial Security in Adulthood

Abstract: This study provides an evidence-based link between adverse childhood experiences (ACEs) and adult financial wellbeing. Drawing on a comprehensive financial wellbeing framework that was developed by the Consumer Financial Protection Bureau, we analyze data from the Behavioral Risk Factor Surveillance System, a survey designed primarily to measure health behaviors and outcomes, but which also asks about financial wellbeing aspects such as food and housing security. We use ordered probit analysis to investigate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(29 reference statements)
0
11
0
1
Order By: Relevance
“…In a recent cross-sectional online survey in an Austrian sample, no work and low income were predictors for higher symptoms of depression and anxiety during the pandemic [ 16 ], just as discontinued working activity in an Italian sample [ 43 ] and economic stressors in a US sample [ 15 ]. ACEs are known to increase the risk for a lower household income, but also financial wellbeing and financial literacy [ 31 ]. The modifying effect of income loss on change of depressive symptoms during the pandemic was even higher compared to ACEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent cross-sectional online survey in an Austrian sample, no work and low income were predictors for higher symptoms of depression and anxiety during the pandemic [ 16 ], just as discontinued working activity in an Italian sample [ 43 ] and economic stressors in a US sample [ 15 ]. ACEs are known to increase the risk for a lower household income, but also financial wellbeing and financial literacy [ 31 ]. The modifying effect of income loss on change of depressive symptoms during the pandemic was even higher compared to ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Lower social support, associated to the experience of childhood adversity [ 28 ], was shown to mediate the association between ACEs and mental health [ 29 , 30 ]. ACEs are associated with lower household income, but also with financial wellbeing and financial literacy [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential associations between ACEs, material hardship, and breastfeeding are complex and warrant future research. ACEs may put individuals at increased risk for material hardship (Harter & Harter, 2021); similarly, material hardship can increase trauma risk (Conrad-Hiebner & Byram, 2020). Mediators for these relationships vary and include physical and mental health challenges, limited support, and other social determinants of health that can create barriers to breastfeeding goals (Watson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that analyze how games and simulations in business or economics classes promote students' awareness and enthusiasm. Harter and Harter (2010) studied financial literacy among high school students and revealed that stock market simulations can significantly enhance financial knowledge among these students. Cebula and Toma (2002) discovered that these sorts of activities have a beneficial effect on students.…”
Section: Literature Reviewmentioning
confidence: 99%